2020
DOI: 10.1021/acs.jpcc.0c08903
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pt Atom Addition to Gas Phase Ce2On Clusters Using Photoionization Efficiency Spectroscopy and Density Functional Theory

Abstract: Photoionization efficiency spectra for PtCe2O n (n = 0–1) clusters were recorded and compared with simulations based on density functional theory to determine adiabatic ionization energies (IE) and verify cluster structures. Calculated structures were also presented for PtCe2O2–5, though no comparison with experiment was made due to nondetection of these species in the mass spectrum. The IEs of PtCe2 and PtCe2O were determined to be 4.59 and 4.55 eV, respectively. The calculated IEs for PtCe2O2–5 sharply rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The PIE spectra for La 9 and La 10 are wider in width and exhibit oscillatory behavior which could be due to the presence of multiple low-lying geometrical isomers in the thermally excited molecular beam, each having a different ionization threshold. A theoretical consideration of all potential PIE transitions, like it was done for small clusters of PtCe 2 and PtCe 2 O, 35 would help better understand these spectra. We have fitted the experimental data to a single curve, though to extract the VIE, ignoring the oscillatory part.…”
Section: Resultsmentioning
confidence: 99%
“…The PIE spectra for La 9 and La 10 are wider in width and exhibit oscillatory behavior which could be due to the presence of multiple low-lying geometrical isomers in the thermally excited molecular beam, each having a different ionization threshold. A theoretical consideration of all potential PIE transitions, like it was done for small clusters of PtCe 2 and PtCe 2 O, 35 would help better understand these spectra. We have fitted the experimental data to a single curve, though to extract the VIE, ignoring the oscillatory part.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed cerium-platinum materials are found in an interesting array of applications ranging from catalysis to magnetic materials and heavy fermion conductors. The report from Bruix et al more than a decade ago, which detailed how strong interactions between Pt nanoparticle catalysts and CeO 2 support material resulted in enhanced activity toward the water-gas shift reaction, was followed by numerous studies geared toward characterizing the catalyst-support interactions. In addition, Ce-doped Pt, Pt-doped ceria, and CeO 2 nanostructure-supported single Pt atoms , have shown desirable properties as catalysts. In a closely related vein, research on Pt nanoparticles on defect-rich surfaces, , and the interactions of other metals, like Au, when supported on ceria, has also been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed Ce x V x′ O y + clusters have been studied by Asmis and co-workers using vibrational predissociation spectroscopy, which showed how the reducibility of Ce 4+ is an important factor governing the promoting role of ceria as a catalyst support material . Photoionization efficiency studies on transition metal-doped cerium oxide clusters, MCe x O y have shown how charge accumulation by the M centers evolves with cerium cluster oxidation ( y ). Mixed Ce–Pt oxide clusters were also probed by Ray et al using anion PE spectroscopy . Mafuné and co-workers’ reactivity studies on mixed Ce x V x′ O y + showed O 2 desorption and preferential oxidation states of +4 and +5 .…”
Section: Introductionmentioning
confidence: 99%